Validity of Kohler's rule for the magneto-resistance in pristine and irradiated NbAs2. (January 2020) - Harimohan, V.; Bharathi, A.; Babu, P.D.; Rajaraman, R.; Magudapathy, P.; David, C.; Sundar, C.S.
Abstract: The synthesis, characterization and magneto-transport investigations on the single crystals of semimetal NbAs2 in a temperature range varying from 300 K to 2.5 K with a magnetic field up to 14 T are reported. The temperature dependence of resistivity that exhibits a metallic behavior without a magnetic field is seen to show an upturn as the magnetic field is applied resulting in a very large magneto-resistance. The upturn temperature displays a systematic increase with increasing fields. It is shown that this behavior of magneto-resistance can be understood in terms of the Kohler's scaling relation rather than in terms of the existence of a critical magnetic field inducing a metal to insulator transition. Through careful experiments, including angular dependence of magneto-resistance, it is verified that NbAs2 does not show negative longitudinal magneto-resistance, a characteristic of Weyl semimetal. Highlights: Magneto-resistance in NbAs2 is studied in as grown and ion irradiated single crystals. Kohler's scaling method is consistently applied to understand the magneto-resistance behavior. By angular magneto-resistance measurements the absence of negative magneto-resistance confirmed. Verified that NbAs2 is not a Weyl semimetal. Quantum oscillations in magnetization.